2022
DOI: 10.1097/bpo.0000000000002062
|View full text |Cite
|
Sign up to set email alerts
|

MRI Predictors of Residual Dysplasia in Developmental Dysplasia of the Hip Following Open and Closed Reduction

Abstract: Background: Following open or closed reduction for children with developmental dysplasia of the hip, there remains a significant risk of residual acetabular dysplasia which can compromise the long-term health of the hip joint. The purpose of this study was to use postoperative in-spica magnetic resonance imaging (MRI) data to determine factors predictive of residual acetabular dysplasia at short-term follow-up. Methods: We retrospectively reviewed 63 hips in 48 patients which underwent closed or open reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…And 4 of them were not available for full text, 17 studies did not match the subject, and 9 studies could not extract the 2 × 2 contingency table. Finally, 9 studies were included for qualitative synthesis ( 18 , 27 34 ) and 6 studies for quantitative synthesis ( 18 , 28 , 29 , 31 , 33 , 34 ). The search process and results are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And 4 of them were not available for full text, 17 studies did not match the subject, and 9 studies could not extract the 2 × 2 contingency table. Finally, 9 studies were included for qualitative synthesis ( 18 , 27 34 ) and 6 studies for quantitative synthesis ( 18 , 28 , 29 , 31 , 33 , 34 ). The search process and results are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The information from the 6 quantitatively synthesized studies is shown in Table 2 . Among them, there were 4 studies in the CAI group ( 18 , 28 , 31 , 34 ) and 4 studies in the CCE group ( 18 , 28 , 29 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that US is a useful and easy method for screening and early diagnosis of DDH. However, to evaluate the therapeutic effect following open and closed reduction, magnetic resonance imaging (MRI) is typically performed to confirm the concentric reduction and predict prognosis (24,29). At this point, for severe DDH that needs reduction, the US results of femoral head size and femoral head ossification may be reproduced by MRI images.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review found that the risk of residual acetabular dysplasia was higher in older patients, female patients, and patients with elevated cartilaginous acetabular indices on MRI 25 . A study of 108 infants with hip dysplasia found that elevated acetabular indices on radiographs before treatment were associated with residual acetabular dysplasia after Pavlik harness treatment 26 .…”
Section: Hip Infant Hip Dysplasiamentioning
confidence: 99%